The Role of Imagery in Enhancing Basketball Learning: A Psychological Approach-Systematic Literature Review - Damayanti, Nadia Fadilla; Rahmat, Alit; Ginanjar, Afan; Siahaan, Derry Renanda Putra Siahaan (Journal of Sport Science and Fitness, 2024)
Physical education learning, particularly in basketball, does not rely solely on physical aspects but also demands mental readiness, concentration, and technical visualization. A psychological approach through imagery or mental imagery is believed to enhance students’ technical skills in sports. This study aims to examine the role of imagery in developing basketball learning through a psychological perspective using the Systematic Literature Review (SLR) method. Data were collected by searching scientific articles in the Google Scholar database using the Harzing’s Publish or Perish application with the keywords “Sports Imagery and Basketball Learning,” and filtered using the Covidence platform within the publication range of 2017–2024. Inclusion criteria included articles written in Indonesian, indexed in SINTA, and focused on students or teachers in physical education. From a total of 200 articles retrieved, 12 were further screened, and 6 articles were deemed relevant for analysis. The analysis followed the PRISMA model and included a quality assessment of the selected articles. The review findings show that imagery is highly effective in improving technical skills in physical education, especially in basketball learning. The use of imagery techniques also enhances students’ concentration, self-confidence, and tactical understanding during the learning process. In conclusion, imagery is an effective mental training method and can serve as an alternative learning strategy in physical education, particularly in basketball, and is recommended to be combined with physical training for optimal results.